ANALISA VARIASI SUHU PADA PROSES DESTILASI BIOETANOL DARI BIJI JAGUNG - Rangga Bayu; A’rasy Fahruddin; Rachmat Firdaus; Edi Widodo (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
The increasing demand for renewable energy has encouraged research into the development of bioethanol from abundant local raw materials, one of which is corn kernels which are rich in starch. This study was conducted to determine the effect of variations in distillation temperature on the volume and purity of bioethanol produced from fermented corn kernels. The research process begins with material preparation, namely sowing corn kernels until they germinate, grinding, then fermenting with yeast (Saccharomyces cerevisiae) for 7 days. The fermentation results were then distilled for 30 minutes using a simple distillation apparatus with three temperature variations, namely 70°C, 80°C, and 90°C. The volume of bioethanol was measured using a measuring cup, while the ethanol content was tested using an alcohol meter. The results showed that at a temperature of 70°C a volume of 130 ml of bioethanol was obtained with a purity of 67%, at a temperature of 80°C a volume of 168 ml was obtained with the highest purity of 83%, while at a temperature of 90°C the volume increased to 191 ml but the purity decreased to 73%. The data demonstrates a trade-off between ethanol volume and purity, where higher heating temperatures increase volume, but purity does not always increase. This study concludes that the optimal distillation temperature is 80°C, as lower energy can produce bioethanol with a combination of a relatively large volume and the highest purity.